Precocious puberty: not only a matter of age - Núñez Almache, Oswaldo (2015)
The onset of puberty in girls has been occurring each time at a younger age, generating concern among parents and seeking healthcare for possible precocious puberty. Nowadays diagnosis of central precocious puberty (CPP) and early puberty onset have chronological cutoff points established over five years ago and despite secular changes described in various populations of the world. The importance of differentiating a physiological event from a pathogenic one is mainly because of the need of timely decision to begin treatment in order to prevent height compromise, reproductive system alterations and risk of future diseases like cardiovascular disease and breast cancer in adulthood. Limits for puberty onset based on biostatistics in normal population should not be applied only to establish limits of chronological age because the risk of a wrong diagnosis. In this article physiological and pathological events of puberty in girls will be reviewed; agreements and disputes described in scientific literature will be presented.